2019
DOI: 10.1111/jcmm.14055
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Golgi phosphoprotein 73 blocks the trafficking of matrix metalloproteinase‐2 in hepatocellular carcinoma cells and inhibits cell invasion

Abstract: Golgi phosphoprotein 73 ( GP 73) has been regarded as a novel serum biomarker for the diagnosis of hepatocellular carcinoma ( HCC ) in recent years. It has been reported that the upregulation of GP 73 may promote the carcinogenesis and metastasis of HCC ; however, the mechanisms remain poorly understood. In this study, GP 73 correlates positively with matrix metalloproteinase‐2 ( MMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Emerging evidence suggests that the Golgi apparatus (GA) can directly or indirectly affect intracellular Ca 2+ fluxes, ROS, metabolism, intra-organelle pH, protein and membrane trafficking and thereby contribute to cell migration/invasion [[21], [22], [23], [24], [25]]. Although these roles have been ascribed to the GA, the intricate molecular mechanisms involved in the control of such processes are still mostly unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that the Golgi apparatus (GA) can directly or indirectly affect intracellular Ca 2+ fluxes, ROS, metabolism, intra-organelle pH, protein and membrane trafficking and thereby contribute to cell migration/invasion [[21], [22], [23], [24], [25]]. Although these roles have been ascribed to the GA, the intricate molecular mechanisms involved in the control of such processes are still mostly unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…GP73 is a biomarker in advanced liver disease. GP73 levels are associated with various liver diseases such as hepatic fibrosis, liver cirrhosis [10], HCC [11] and HBV mediated acute on top of chronic liver failure [12 & 13] and tumor metastasis prediction [14]. This study aimed to assess the value of serum GP73 in diagnosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of GP73 blocks the trafficking of intracellular MMP-7 and leads to repression of cancer cell invasion. Furthermore, in our recent study, it has been proved that GP73 is involved in the trafficking of intracellular MMP-2, a factor playing comparable functional roles to MMP-7 19 . Both of the two factors interact with GP73 in the region of cytoplasmic domain, therefore MMPs might act as potential substrates for GP73-mediated protein trafficking and facilitate HCC metastasis.…”
Section: Discussionmentioning
confidence: 88%
“…As previously reported, GP73 is highly expressed in most types of cancers, especially in HCC, and it has been adopted clinically as a cancer biomarker for decades 15,16 . In most recent studies, it was discovered that high expression of GP73 facilitates cancer metastasis by promoting epithelial-mesenchymal transition (EMT), and evidence has implicated that GP73 is not only a serum biomarker but also an important player in carcinogenesis and metastasis 1719 . Viral infection is reportedly to activate the expression of GP73 in HCC cells; however, it has also been indicated that GP73 is upregulated in cancer cells without viral infection, such as non-viral-related HCC, bladder cancer and prostate cancer 2022 .…”
Section: Introductionmentioning
confidence: 99%